Enhancing the performance of iron-based binders with seawater and CO2 sequestration - V Chandralega; M Shanmugasundaram; David Stone (Case Studies in Construction Materials)
This study explores CO₂ mineralization and sequestration in a sustainable iron-based binder formulated with industrial wastes such as iron dust, fly ash, calcium carbonate, and metakaolin, along with oxalic acid variations of 0 %, 2 %, and 4 % to form complex iron carbonates. The samples were cured under controlled CO2 conditions and evaluated through compressive strength tests, and microstructural analysis, XRD, and FTIR results. In this study normal water and seawater were employed as the CO₂-capturing media, enabling mass transfer for reactions under ambient conditions. Experimental results showed that 2 % oxalic acid in potable water and 4 % oxalic acid in seawater yielded the maximum compressive strength after 28 days. Microstructural analysis revealed that oxalic acid enhanced the matrix densification and mechanical strength by promoting siderite and calcite formation through improved ion dissolution, whereas its absence led to decreased CO2 diffusion and reduced mechanical strength. Seawater with its high alkalinity and mineral content, significantly augmented the carbonation efficiency, validating its potential as an effective medium for sustainable binders in CO2 sequestration.